If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2-8x+7=(x-1)
We move all terms to the left:
x2-8x+7-((x-1))=0
We add all the numbers together, and all the variables
x^2-8x-((x-1))+7=0
We calculate terms in parentheses: -((x-1)), so:We get rid of parentheses
(x-1)
We get rid of parentheses
x-1
Back to the equation:
-(x-1)
x^2-8x-x+1+7=0
We add all the numbers together, and all the variables
x^2-9x+8=0
a = 1; b = -9; c = +8;
Δ = b2-4ac
Δ = -92-4·1·8
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{49}=7$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-7}{2*1}=\frac{2}{2} =1 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+7}{2*1}=\frac{16}{2} =8 $
| (w-2)^2-63=0 | | 29=-6+1.5x+3.5x | | x^2-590x+45000=0 | | (1/3)b-2=6-(1/2)b | | 6r+2r=8+4r | | P+14=8p+56 | | 8p-5=6p+1 | | t=-16t^2+48t+3 | | 9x-18=4x-36 | | -3g^2-12g=1+g | | a/9+9=10 | | 3x+x+2x=42 | | 12x+2{15+11(-10x+14)}=4(12x-5) | | 5x-3x+18=-32 | | -8x-65=0 | | 3x+2=-55 | | -9-3x+4x-24=4 | | Y=-5x+3x+10 | | 5m/8+15=27 | | 12x+2(15+11(-10x+14))=4(12x-5) | | j4– 2= 1 | | 2xx=5 | | 12x+215+11(-10x+14)=4(12x-5) | | 7x+1+19=12x-5 | | w+2/7=13/14 | | 12-5(3r+)=17 | | 6m=12=42 | | 6.5y−19=2.5(y−4 | | -6.5+7d=-9.5(6.5d-8) | | 4x/3=27/x | | 6.5y−19=2.5(y−4) | | -8=x/3-2 |